Studying Housework Across Nations. Issue 2 (3rd June 2013) - Treas, Judith; Lui, Jonathan
Abstract : Long motivated by microlevel paradigms, the study of housework has been revitalized by research emphasizing macrolevel influences. Common trends and persistent differences across the developed world underscore the importance of country context. Gender specialization, gender equality, and socioeconomic (in)equality are cultural and structural domains that channel domestic behavior in predictable directions. By demonstrating the country‐to‐country differences in the causes and consequences of domestic arrangements, this research points to 5 questions that set a course for studies of housework in comparative context .